PennDemic Simulation Framework: An Innovative Approach to Increase Student Interest and Confidence in Disasters Preparedness/Response and Interdisciplinary Teamwork - Cole, Stephen D.; Nelson, Hillary C. M.; Jenkins, Bonnie D.; Poon, Cathy Y.; Rankin, Shelley C.; Becker, Deborah E. (Frontiers in Public Health, 2021)
An interdisciplinary group from two higher-education institutions in Philadelphia developed a novel framework for interprofessional education. This framework was applied to two different scenarios disease outbreak and natural disaster, which were used in simulations in 2018 and 2020. By design, these simulations included students from a broad range of disciplines, beyond the typical healthcare fields. Students were first grouped by discipline and were then placed in interdisciplinary teams for the rest of the scenario. Students were administered four surveys throughout which included 10 point-Likert scale and free response items. A statistically significant post-simulation increase in student interest and confidence was found. Survey analysis also revealed higher scores of positive group behaviors among interdisciplinary teams when compared to discipline groups. Importantly, students realized the importance of broad representation of disciplines for disaster preparedness. The PennDemic framework may be helpful for teams looking to develop simulations to build interest and confidence in disaster preparedness/response and interdisciplinary teamwork.